Practical Synthesis of Precursors of Cyclohexyne and 1,2-Cyclohexadiene - Nakura, Ryo; Inoue, Kazuki; Okano, Kentaro; Mori, Atsunori (Synthesis, 2019)
This study investigated a practical method for regiocontrolled synthesis of precursors of strained cyclohexynes and 1,2-cyclohexadienes, which is a one-pot procedure consisting of a rearrangement of silyl enol ether and subsequent formation of the enol triflates. Triethylsilyl enol ether, derived from cyclohexanone, was treated with a combination of LDA and t-BuOK in n-hexane/THF to encourage the migration of the silyl group to generate an α-silyl enolate. Subsequently, the α-silyl enolate was reacted with Comins’ reagent to yield the corresponding enol triflate. Finally, the α-silylated trisubstituted lithium enolate for the synthesis of 1,2-cyclohexadiene precursor was isomerized in the presence of a stoichiometric amount of water for one hour at room temperature to exclusively provide tetrasubstituted lithium enolate for the synthesis of cyclohexyne precursor in one pot.
Keywords: strained molecules; allenes; alkynes; enolate; isomerization; lithiation; rearrangement; solvent effects